A Step Size Preserving Directed Mutation Operator - Berlik, Stefan (Genetic and Evolutionary Computation – GECCO 2004. Genetic and Evolutionary Computation Conference, Seattle, WA, USA, June 26-30, 2004. Proceedings, Part I)
Using a directed mutation can improve the efficiency of processing many optimization problems. The first mutation operators of this kind proposed by Hildebrand [1], however, suffer from the asymmetry parameter influencing the mutation step size. Extreme asymmetry can lead to infinite step size. The operator presented here overcomes this drawback and preserves the step size.